Human Brotherhood is the Key to Ensuring Interreligious Dialogue (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Tolerance, pluralism, mutual respect and diversity of religions and beliefs contribute to human brotherhood. In addition, it is becoming increasingly important to become familiar with different cultures and religions or beliefs and to educate in a spirit of tolerance that ensures that society recognizes and respects religious and cultural diversity, including in matters of religious expression.